Peningkatan Prestasi Belajar Matematika Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Think-Pair-Share (TPS) Siswa Kelas VIII-2 UPT SMP Negeri 1 Alla Kabupaten Enrekang - Nurhayati Nurhayati (CV. Syntax Corporation Indonesia, 2022)
Mathematics is a language that symbolizes a series of meanings from the statements that we want to convey. The reality on the ground illustrates that during the learning process, most of the students are less active, they will be active when given assignments, do not pay attention to the teacher's explanation, many students do not finish working on the questions in the allotted time. Students also seem unmotivated in mathematics. In addition to the growth of motivation, teachers must also generate motivation in students to be stimulated to learn the material and want to understand further lessons. This research formulates a problem. Is the application of the TPS type cooperative learning model able to improve mathematics learning achievement in circle material in class VIII-2 UPT SMP Negeri 1 Alla?. This study aims to improve the mathematics learning achievement of grade VIII-2 UPT SMP Negeri 1 Alla students in the circle material through the application of the TPS type cooperative learning model. TPS learning can develop the ability to express ideas or ideas verbally and compare them with other people's ideas. Students can develop the ability to test their own ideas and understanding and receive feedback. The interactions that occur during learning can increase motivation and provide stimulation to think so that it is beneficial for the long-term educational process. This research is a Classroom Action Research (CAR). The data analysis technique used to analyze the collected data is a comparative descriptive technique, which is to compare success between cycles. The technique of analyzing student achievement data uses simple statistics, namely the analysis of learning completeness. From the results of data analysis and discussion, it is concluded that the application of the Think Pair Share type of cooperative learning model on the circle material has been proven to improve student achievement in class VIII-2 UPT SMP Negeri 1 Alla. learning in class VIII-2 UPT SMP Negeri 1 Alla.